Distribution of causative microorganisms in diabetic foot infections: a ten-year retrospective study in a tertiary care hospital in central Malaysia - Hanachi, Parichehr; Rampal, Sanjiv; Neela, Vasantha Kumari; Cheema, Manraj Singh; Sarawan Singh, Sandeep Singh; Tan, Eng Kee; Sinniah, Ajantha (MDPI, 2023)
Diabetes mellitus is a global pandemic, especially in Southeast Asia. Diabetic foot infection (DFI) is a common complication of this condition and causes significant morbidity and mortality in those affected. There is a lack of locally published data on the types of microorganisms and empirical antibiotics being prescribed. This paper highlights the importance of local microorganism culture and antibiotic prescription trends among diabetic foot patients in a tertiary care hospital in central Malaysia. This is a retrospective, cross-sectional study of data taken from January 2010 to December 2019 among 434 patients admitted with diabetic foot infections (DFIs) using the Wagner classification. Patients between the ages of 58 and 68 years old had the highest rate of infection. Pseudomonas Aeruginosa, Proteus spp., and Proteus mirabilis appeared to be the most isolated Gram-negative microorganisms, and Staphylococcus aureus, Streptococcus agalactiae, and MRSA appeared to be the most common Gram-positive microorganisms. The most common empirical antibiotics prescribed were ampicillin/sulbactam, followed by ciprofloxacin and ceftazidime, and the most common therapeutic antibiotics prescribed were ampicillin/sulbactam, ciprofloxacin, and cefuroxime. This study could be immensely pertinent in facilitating future empirical therapy guidelines for treating diabetic foot infections.